Contemporary archaeology in theory (Chichester, U.K. ; Malden, Mass.)
xix, 637 sayfa
Keywords: “The second edition of Contemporary Archaeology in Theory: The New Pragmatism, has been thoroughly updated and revised, and features top scholars who redefine the theoretical and political agendas of the field, and challenge the usual distinctions between time, space, processes, and people. [This edition:] defines the relevance of archaeology and the social sciences more generally to the modern world; challenges the traditional boundaries between prehistoric and historical archaeologies; discusses how archaeology articulates such contemporary topics and issues as landscape and natures; agency, meaning and practice; sexuality, embodiment and personhood; race, class, and ethnicity; materiality, memory, and historical silence; colonialism, nationalism, and empire; heritage, patrimony, and social justice; media, museums, and publics; examines the influence of American pragmatism on archaeology; offers 32 new chapters by leading archaeologists and cultural anthropologists.” --